Influence of three alkalizing agents on some functional properties of cassava starch modified using epichlorohydrin - Daramola, B; Bamidele, EA (Bangladesh Journal of Scientific and Industrial Research, 2015)
Influence of three alkalizing agents namely, potassium hydroxide (KOH) , ammonium hydroxide (NH4OH), and dimethyl sulphoxide (DMSO) during modification as modification facilitator on some functional properties of cassava starch modified using epichlorohydrin (EPI) at room temperature was studied. Assessment of the principal functional property; pasting properties and associated pasting indices of technological importance, notably peak viscosity and set back viscosity. The low peak viscosity (RVU) of the cassava EPI-modified starch ranged from 119.67-178.17; 128.50-161.17 for samples alkalized using KOH and DMSO respectively in comparison to the high peak viscosity (RVU) of the native starch. NH4OH was less effective alkalizing agent under the conditions used in this study. Cassava- EPI modified starch showed improved paste stability expressed in breakdown viscosity (RVU) values of 22.08-48.75 and 37.92-55.58 for KOH and DMSO alkalized samples respectively. Evaluation of other functional properties such as swelling power, apparent viscosity and paste clarity of the cassava-EPI modified starch showed alkaline-type dependent cross linkage activity of EPI. Assessment of all the functional properties of starch accomplished under the conditions employed in this study revealed that irrespective of concentration of EPI added, activity of alkalizing reagents is in the order: KOH>DMSO>NH4OH. DOI: http://dx.doi.org/10.3329/bjsir.v49i2.21997 Bangladesh J. Sci. Ind. Res. 49(2), 63-68, 2014